Structure-to-function prediction and cloning of KPN_02816 (yfgC) hypothetical protein of klebsiella pneumoniae MGH78578 pathogen - Hasni, Nur Amalia (2015)
Klebsiella pneumoniae is a dangerous pathogen that causes many healthcare-associated infections. In 2006, the complete genome of Klebsiella pneumoniae subsp. pneumoniae MGH 78578 was sequenced and 21% of the total 4894 genes in the genome encodes for hypothetical proteins (HPs). In general HPs are referred as proteins of unknown function which they are predicted to be expressed from an open reading frame, but there is no experimental evidence expressed in vivo. Analyzing, annotating and characterizing these hypothetical proteins will bring insight to their functions which will lead to new discoveries of their structures, functions and applications. Previously, an HP termed KPN_02816 was identified to be a „hypothetical protease‟ with 99% sequence identity to peptidase M48 family from this pathogen. As proteases have been reported to play a role in conferring pathogenicity, this present study further the investigation of predicting the structure and function of KPN_02816 as well as cloning the gene into E. coli DH5α for its production and in vitro biochemical characterization. Bioinformatics analyses using CDD, PFAM, MEROPS, PDB, and BLAST programs on the sequence of KPN_02816 sequence showed that the HP has functionally important domains such as peptidase family M48, TPR (tetratricopeptide repeat) domain, TPR_14 (tetratricopeptide repeat) and putative zinc dependent protease. Prediction of its 3D structure by I-TASSER revealed that it resembles the crystal structure of APC/C heterotetramer Cut9-Hcn1 (PDB ID: 2XPIA) using the predicted template of x-ray structure of the putative zinc dependent peptidase Q74D82 at resolution 1.7Å (PDB ID: 3C37A). TM-score predicted was 0.929 and the RMSD value is 1.10 Å when model 1 is aligned with 2XPIA. The open reading frame of KPN_02816 was synthesized with the incorporation of EcoRI and HindIII at 5‟ and 3‟ end, respectively and was cloned into pUCIDT AMP cloning vector and subsequently into pET-28b(+) expression vector for production of the protein in E. coli BL21(DE3).